Sumber Pakan Berkualitas: Pemanfaatan Kotoran Olahan Bandeng Presto dalam Pemeliharaan Pakan Hewan Ternak dan Tanaman - Asmara, Yefira Octavina; Ellyana, Silvia; Wardana, Labib Fakhri Dwi; Ningrum, Dian Eka Aprilia Fitria (Experiment: Journal of Science Education, 2023)
Quality Feed Source: Utilization of Processed Presto Milkfish Manure in Raising Livestock and Plants. The article resulting from this research describes the processing of pressure-cooked milkfish waste for livestock feed and plant development. The research used descriptive qualitative methods based on data from the environment of the presto milkfish waste processing site, namely a catering business in the Kepanjen area, Malang Regency, with the aim of finding out that milkfish waste has nutritious substances which are very beneficial for the growth of animals and plants. After processing the waste Presto milkfish also does not leave waste in any form that can pollute the surrounding environment. Milkfish parts other than meat, such as the head, fins and innards (fillings) of milkfish can be processed by boiling them into a feed mixture for livestock such as chickens, ducks, ducks, etc. Apart from that, the boiled water from the fish parts can also be used as liquid fertilizer which is mixed with dry leaves and then poured onto plants to improve the growth and quality of the fruit, such as chilies and shallots